Changes in Nutritional Status of Children with Acyanotic Congenital Heart Disease Six Months After Repair and Intervention - Siregar, Ludwina Rouli Hilary; Heroe Soebroto; Hidayat, Taufiq (Universitas Airlangga, 2026)
Background: Acyanotic congenital heart diseases (CHDs) namely, atrial septal defect (ASD), ventricular septal defect (VSD), and patent ductus arteriosus (PDA) are prevalent in children and often associated with malnutrition due to increased metabolic demands and feeding difficulties. Aims: This study evaluated the incidence, characteristics, and nutritional outcomes of paediatric patients undergoing repair for acyanotic CHD at RSUD Dr. Soetomo in 2023. Methods: A retrospective observational study included 40 children aged 1–13 years with ASD, VSD, PDA, or combinations thereof. Data on age, sex, and anthropometric parameters including weight-for-age (WAZ), height-for-age (HAZ), weight-for-height (WHZ), and BMI-for-age (BAZ) were assessed before and at 1, 3, and 6 months post-repair. Results: PDA was the most frequent diagnosis (50%), with females comprising 60% of cases and most patients (62.5%) under 5 years. Before repair, 71.4% were underweight and 60% were stunted (mean WAZ –2.58; HAZ –2.3). Nutritional recovery occurred gradually; at 6 months, normal WAZ increased to 58.8% and normal HAZ to 65%, though 38.2% remained underweight and 35% stunted. Conclusion: Repair intervention improves but does not fully normalize nutritional status. Ongoing nutritional support and long-term monitoring are essential for optimal recovery in paediatric CHD patients. – Highlights: 1. Nutritional status among paediatric patients with acyanotic congenital heart disease (ASD, VSD, PDA) significantly improved within 6 months post-repair, especially in weight-for-age and height-for-age indicators, demonstrating the beneficial impact of surgical correction on growth recovery. 2. Despite overall improvement, over one-third of patients remained underweight or stunted six months after repair, emphasizing the need for continued nutritional monitoring and integrated dietary support in post-operative care programs.